The Impact of Corporate Social Responsibility Practices through Supply Chain Management on Company Risk in Indonesia - Syahputra Silalahi, Amlys; Dalimunthe, Doli Muhammad Jafar; Sariartha Sianipar, Aryanti; Saputra, Jumadil (International Journal of Supply Chain Management, 2020)
This study aims to examine the impact of the supply chain strategies on company risk in the emerging market, Indonesia. The samples of this study are companies listed in Indonesia Stock Exchange in 2018. According to the sampling procedure, there were 458 companies that employed corporate social responsibility during this period. The corporate social responsibility score were obtained from the content and risk analysis represented by the market-based risk such as systematic risk, idiosyncratic risk, and total risk. The findings from the data analysis show that there was no CSR significant impact on company's idiosyncratic and systematic risk. However, it has a weak negative impact on total risk. The CSR dimensions that affect company risk are supply chain partnerships and tax contributions. The supply chain partnerships are negatively associated with company's systematic and idiosyncratic risk. This finding was also consistent after adding the control variables. On the contrary, tax contributions are positively associated with higher systematic and idiosyncratic risk to the company.